2013
DOI: 10.1007/s00425-013-1848-6
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous post-transcriptional gene silencing of flavone synthase resulting in high accumulation of anthocyanins in black dahlia cultivars

Abstract: Black color in flowers is a highly attractive trait in the floricultural industry, but its underlying mechanisms are largely unknown. This study was performed to identify the bases of the high accumulation of anthocyanidins in black cultivars and to determine whether the high accumulation of total anthocyanidins alone leads to the black appearance. Our approach was to compare black dahlia (Dahlia variabilis) cultivars with purple cultivars and a purple flowering mutant of a black cultivar, using pigment and mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
43
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 41 publications
(45 reference statements)
4
43
0
Order By: Relevance
“…Our general understanding is that flavonoid accumulation is largely controlled at the transcriptional level by transcription factors regulating the expression of the pathway structural genes (Hartmann et al, 2005;Koes et al, 2005). However, pathway regulation downstream to the transcriptional level is less understood (Tanaka and Uritani, 1977;Pairoba and Walbot, 2003;Deguchi et al, 2013). Lately, Kelch domain-containing F-box (KFB) proteins were shown to be involved in regulation of the phenylpropanoid pathway (Shao et al, 2012;Zhang et al, 2013Zhang et al, , 2015.…”
mentioning
confidence: 99%
“…Our general understanding is that flavonoid accumulation is largely controlled at the transcriptional level by transcription factors regulating the expression of the pathway structural genes (Hartmann et al, 2005;Koes et al, 2005). However, pathway regulation downstream to the transcriptional level is less understood (Tanaka and Uritani, 1977;Pairoba and Walbot, 2003;Deguchi et al, 2013). Lately, Kelch domain-containing F-box (KFB) proteins were shown to be involved in regulation of the phenylpropanoid pathway (Shao et al, 2012;Zhang et al, 2013Zhang et al, , 2015.…”
mentioning
confidence: 99%
“…The C* and L* of each anthocyanin showed similar tendencies between pH 5.0 and pH 5.5 (Fig. 1), which corresponded to the petal pH of relatively deeper cyanic (purple, red, and black) cultivars (pH 4.9-5.5, Deguchi et al, 2013;Ohno et al, 2013). These results suggested that the order of the contribution should be consistent, and the color of Pg 3MG5G was always the farthest from black among the four anthocyanins in this petal pH range.…”
Section: The Reason Why High Accumulation Of Cy-based Anthocyanins Ismentioning
confidence: 69%
“…However, the proportion of Cy varied among the cultivars, wherein 'Fidalgo Blacky' had the highest proportion. This characteristic suggested that Cy-based anthocyanins contribute more to black flower coloring [described as the difference of "darkness unit" in Deguchi et al (2013)]; petal L* and C* are lowered more by Cy-based anthocyanins than Pg-based anthocyanins in dahlias.…”
Section: Introductionmentioning
confidence: 99%
“…In the pathway leading to anthocyanins and flavones, cyanidin and luteolin are synthesized via flavonoid 3 0 -hydroxylase (F3 0 H) activity as counterparts to pelargonidin and apigenin, respectively (Ayabe and Akashi 2006;Tanaka and Brugliera 2013). In dahlia, these enzymes have been studied (Fischer et al 1988;Wimmer et al 1998;Halbwirth et al 2008;Thill et al 2012) and the genes encoding the enzymes have been isolated (Schlangen et al 2010b;Ohno et al 2011a, b;Deguchi et al 2013). In addition, a bHLH transcription factor, DvIVS, regulates anthocyanin levels by regulating the expression of DvCHS1, DvF3H, DvDFR, and DvANS (Ohno et al 2011a.…”
Section: Introductionmentioning
confidence: 96%